Patient and caregiver experiences with hydrocortisone injections in adrenal crisis: a mixed-methods cross-sectional study - Llahana, Sofia; Anthony, Julia; Sarafoglou, Kyriakie; Geffner, Mitchell E.; Ross, Richard (Frontiers in Endocrinology, 2025)
BackgroundAdrenal crisis is the leading cause of death in patients with adrenal insufficiency, and prevention requires immediate parenteral hydrocortisone administration. However, most patients do not receive their home emergency hydrocortisone injection. Our study aimed to investigate barriers and enablers to using emergency hydrocortisone injections in managing adrenal crises.MethodsThis mixed-methods observational study utilized an online survey distributed through two U.S.-based patient advocacy groups. A total of 688 respondents completed the survey, including 485 (70%) parents/caregivers of individuals with adrenal insufficiency and 203 (30%) adults with adrenal insufficiency. Qualitative free-text responses were analyzed using thematic content analysis, with subsequent quantification of identified barriers and enablers to administering parenteral hydrocortisone during adrenal crises.ResultsOver 60% of patients with adrenal insufficiency had required parenteral hydrocortisone for an adrenal crisis, yet fewer than 20% managed to self-inject. Thirteen barriers and nine enablers were identified across three thematic domains: device factors, external factors, and emotional factors. Key barriers included the complexity of the multi-step hydrocortisone injection process (81%), injection-related anxiety and lack of confidence (18%), challenges accessing the correct hydrocortisone formulation or equipment (38%), and inadequate support for managing adrenal crises (29%). Key enablers included the effectiveness of hydrocortisone (14%), the convenience of the combined powder-and-diluent hydrocortisone vial (36%), and patient education (4%). Notably, 97% of participants expressed a preference for a hydrocortisone autoinjector to enhance self-injection capabilities.ConclusionEffective adrenal crisis management requires comprehensive, evidence-based interventions across patient, healthcare, and societal levels. This should include the development of user-friendly hydrocortisone delivery devices, individualized patient education, healthcare system reforms, and public awareness.